Grain productivity of four maize three-way hybrids with andro-esterile and fertile versions. - Tadeo-Robledo, Margarita (2014)
The objective of this study was to evaluate the productivity of maize hybrids developed for The High Valleys of Mexico. Four hybrids in their versions of male-sterile and fertile were evaluated in four uniform experiments using a randomized complete block design, at the Experimental Station of Mexico (CEVAMEX) and the Faculty of Higher Studios Cuautitlan (FESC-UNAM). The statistical analysis was performed in a combined form with the factors: hybrids (4), locations (4), male sterility/fertility versions (2), and the interactions between these factors. Significant differences for genotypes (p≤0.01), for locations and for interaction hybrid x locations (p≤0.05) were detected. The coefficient of variation for seed yield was 21.5% and overall mean was of 6,998 kg/ha. The site CEVAMEX 2009, in its first planting date, produced 8829 kg/ha and surpassed the other three environments. The performance of the four hybrids was similar (p>0.05). The male sterile version had a yield of 7170 kg/ha, similar (p>0.05) to the fertile version (6826 kg/ha), which confirms that the versions of the fertile and male-sterile hybrids of this study are isogenic.